2000
DOI: 10.1152/ajpcell.2000.278.6.c1143
|View full text |Cite
|
Sign up to set email alerts
|

Limited myogenic response to a single bout of weight-lifting exercise in old rats

Abstract: The purpose of the present study was to compare the myogenic response of hindlimb muscles in young (14-20 wk of age) and old (>120 wk of age) rats with a single exhaustive bout of heavy resistance weight lifting. [(3)H]thymidine and [(14)C]leucine labeling were monitored for up to 2 wk after the exercise bout to estimate serial changes in mitotic activity and the level of amino acid uptake and myosin synthesis. Histological, histochemical, and immunohistochemical [anti-5-bromo-2'-deoxyuridine and myogenic dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 32 publications
5
64
0
5
Order By: Relevance
“…Although the latter cannot be ruled out based on the current shortage of published findings, we suggest the former explanation has merit. Several animal studies have demonstrated slowed repair/ regeneration in older vs. young adult animals (8,12,21,43,61). If recovery time is rate limiting in older muscle, one might expect a lesser hypertrophy adaptation in older vs. young adults subjected to the same fairly high loading frequency.…”
Section: Age Differences In Resistance Training-induced Myofiber Hypementioning
confidence: 99%
See 1 more Smart Citation
“…Although the latter cannot be ruled out based on the current shortage of published findings, we suggest the former explanation has merit. Several animal studies have demonstrated slowed repair/ regeneration in older vs. young adult animals (8,12,21,43,61). If recovery time is rate limiting in older muscle, one might expect a lesser hypertrophy adaptation in older vs. young adults subjected to the same fairly high loading frequency.…”
Section: Age Differences In Resistance Training-induced Myofiber Hypementioning
confidence: 99%
“…There are several reports of MRF upregulation in response to various muscle perturbations including stretch overload (11,42), ablation (2, 3), denervation (35), myotoxicity (43), and acute resistance loading (9,22,34,53,61). In a number of these studies, MRF responses and/or muscle repair mechanisms were found to be limited by old age (34,(41)(42)(43)61). This may result from heightened basal levels of MRFs in the aging muscle (7,34,35,49) because MRF expression tends to increase as the degree of sarcopenia advances (17).…”
Section: Effects Of Age On Load-mediated Changes In Regenerative Markersmentioning
confidence: 99%
“…Diante disso, o protocolo de levantamento de peso para ratos, proposto por Tamaki e cols. (43), tem sido utilizado como modelo de exercício resistido de alta intensidade (15), no qual uma sessão do exercício, até a exaustão, é suficiente para desencadear aumento de síntese protéica nos músculos flexores plantares (sóleo, plantar e gastrocnêmio) (15,44). O protocolo de levantamento de peso para ratos em meio líquido é uma variação do modelo proposto por Tamaki e cols.…”
Section: Gruposunclassified
“…A ausência de diferenças estatísticas nas variáveis citadas não estão relacionadas a desajustes no planejamento experimental, já que a utilização de um "n" de seis animais é adequada e suficiente para a reprodução e interpretação dos teores de proteínas e DNA em músculo esquelético (15,45,46). Porém, respostas hipertróficas miofibrilares foram observadas no músculo flexor plantar, com predominância de fibras glicolíticas, em ratos submetidos ao mesmo protocolo experimental por quatro semanas (47).…”
Section: Gruposunclassified
See 1 more Smart Citation